2017
DOI: 10.1128/aac.00962-17
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Formulation of Conventional and Pegylated Meglumine Antimoniate-Containing Liposomes Reduces Inflammatory Process and Parasite Burden in Leishmania infantum-Infected BALB/c Mice

Abstract: Pentavalent antimonial has been the first choice treatment for visceral leishmaniasis; however, it has several side effects that leads to low adherence to treatment. Liposome-encapsulated meglumine antimoniate (MA) arises as an important strategy for chemotherapy enhancement. We evaluated the immunopathological changes using the mixture of conventional and pegylated liposomes with MA. The mice were infected with and a single-dose treatment regimen. Comparison was made with groups treated with saline, empty lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
4
9
0
Order By: Relevance
“…Secondly, it could also be due to the use of liposomes, as empty liposomes reduced the formation of granulomas. A recent study reported that the use of liposomal formulations of meglumine antimoniate was associated with a reduced hepatic tissue response and increased Th1 response [50], which is consistent with the slightly lower granulomatous response observed in mice treated with L-Galf compared to Galf in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, it could also be due to the use of liposomes, as empty liposomes reduced the formation of granulomas. A recent study reported that the use of liposomal formulations of meglumine antimoniate was associated with a reduced hepatic tissue response and increased Th1 response [50], which is consistent with the slightly lower granulomatous response observed in mice treated with L-Galf compared to Galf in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Parasite burden in the spleen was analyzed 30 days after infection by real-time PCR (qPCR) quantification, as described by [ 30 ]. Briefly, at the end of the study, the mice were euthanized, and the spleens were extracted and used for genomic DNA isolation with the CTAB reagent.…”
Section: Methodsmentioning
confidence: 99%
“…(Fajardo et al 2016) but it seems to be successful for Leishmania species. Reports of infection of dogs (Roatt et al 2012), hamsters (Moreira et al 2012b), mice (Reis et al 2017), and sand flies (Agrela and Feliciangeli 2015) demonstrate the potential use of this medium concerning in vivo Leishmania infection.…”
Section: Discussionmentioning
confidence: 94%